Synthesis, anticancer activity, and molecular modeling of 1,4-naphthoquinones that inhibit MKK7 and Cdc25; European Journal of Medicinal Chemistry; Vol. 183 - Shchepyotkin I. A. Igor Aleksandrovich; Karpenko A. S. Alexander; Khlebnikov A. I. Andrey Ivanovich; Shibinska M. O. Marina; Levandovskiy I. A. Igor; Kirpotina L. N. Liliya Nikolaevna; Danilenko N. V. Nadezhda Viktorovna; Quinn M. T. Mark (2019, 2019)
Title screen